'Seven whole days': The Obligation of the Clergy of the Church of England to 'say daily the Morning and Evening Prayer'. (January 2022) - Dewhurst, Russell
Abstract : All Christians are called to pray. The daily offering of Morning and Evening Prayer is a particular obligation of the clergy of the Church of England, as part of the 'manner of life of clerks' laid down in Canon C 26. However, despite the significant time devoted to these prayers by the clergy on a daily basis, there has been little detailed examination of this canonical obligation. This article explores the historical background to the obligation and its effect today.